Widespread gaps in native tree seed supply for ecosystem restoration - Jalonen, Riina; Fremout, Tobias (2025)
Despite growing global investments in ecosystem restoration, seed supply for native tree species remains a major bottleneck, particularly in the Global South where species diversity is high and natural seed sources dwindling due to land use change. • Country-specific availability of site adapted tree seed for restoration can be assessed through a new methodology which combines environmental clustering to define seed zones, Maxent species distribution models for target tree species, and data on existing seed sources. • Application of the method to 21 native pilot species in Bangladesh, India, Indonesia, and the Philippines revealed that, on average, only 34% of seed zones had designated seed sources, despite the species being widely used in restoration. • Almost all seed sources (97%) were predicted to remain within the species’ suitable habitat under future climates, showing that informed investments in establishing seed sources can bring sustained benefits. • The gap analysis methodology enables countries to strategically prioritize areas for seed source development, supporting the achievement of national restoration goals.